Peran Kejaksaan Dalam Tahap Penuntutan Terhadap Anak Yang Melakukan Tindak Pidana Pornografi - Cokorda Istri Ratih Utami Dewi; I Nyoman Putu Budiartha; I Nengah Laba (Fakultas Hukum Universitas Warmadewa, 2019)
present there are many problems that arise in the community that are not only carried out by adults but also carried out by children, one of which is a criminal act of pornography. Children have a special position before the law based on the consideration that children are human beings with all their biological and psychological limitations and have not been able to fight for everything that their rights. So the question arises, namely regarding the role of the Prosecutors in the stage of prosecution and the sanctions for children who commit acts of pornography. The sources of legal material used in this research are primary legal material and secondary legal material. The techniques for collecting legal materials in this research use a study document technique with a card system, namely by recording and understanding the contents of primary legal material and secondary legallmaterial. Analysis of legal material in this research is descriptive analysis. The research method in this research is a type of normative legal research, namely by the legal approach, conceptual approach and case approach. The conclusion that can be drawn is the role of the Prosecutor in the prosecution stage on children who commit act of pornography in accordance with the prosecution stage in general, however there are differences in treatment for children who commit a criminal offense including pornography, that the Prosecutors must have experience as public prosecutor in the general court environment, have an interest, dedication and understanding child issues and have followed the technical appointment of child judiciary. Sanctions imposed on children who commit a criminal offense are criminal sanctions and sanction action. Criminal sanctions (imprisonment) is imposed for children aged 14 years to 18 years, with a maximum imprisonment of 1/2 (one in two) of the maximum imprisonment of adults. Sanctions are imposed for children aged 12 years but not yet 14 years old. Criminal sanctions can not be imposed on children under 12 years old.